Management of chronic myelogenous leukemia with COVID-19 and hepatitis B - Yu, Tian; Li, Weiming; Yu, Tao (Frontiers in Oncology, 2023)
The application of immunosuppressive agents and targeted drugs has opened a novel approach for the treatment of hematological tumors, and the application of tyrosine kinase inhibitors for the treatment of chronic myeloid leukemia is one of the landmark breakthroughs that has considerably improved the prognosis of CML patients. However, with the extensive use of TKI, the co-infection of CML patients has become increasingly apparent, especially regarding infectious diseases such as hepatitis B and COVID-19. The underlying mechanism may be related to the inhibition of the immune function by TKI. Poor management, including disease progression due to the infectious disease or TKI dose reduction or discontinuation, may lead to adverse clinical outcomes and can even be life-threatening. Therefore, this review principally provides an overview of the pathogenesis and standardized management principles of CML patients with comorbid COVID-19 or hepatitis B in order to improve clinicians’ awareness of the risks so as to more effectively diagnose and treat CML and improve the survival rate and quality of life of patients. In the past two decades, owing to the advent of imatinib, chronic myeloid leukemia (CML) has transformed into a chronic controllable disease, and even treatment-free remission can be anticipated. Earlier studies have indicated that tyrosine kinase inhibitor (TKI) exerts a peculiar inhibitory effect on the body’s immune function. Therefore, with the widespread application of TKI, more and more attention has been paid to the comorbidity of infectious diseases in CML patients, especially in patients with progressive disease or non-remission. Despite some studies revealing that the proportion and severity of SARS-CoV-2 infection in CML patients receiving TKI treatment are lower than in patients with other hematological malignancies, CML patients with stable disease are still recommended to be vaccinated against SARS-CoV-2, while TKI may or may not be discontinued. Meanwhile, the management of CML patients during the epidemic of coronavirus disease 2019 (COVID-19) still necessitates further discussion. This article also provides an overview of TKI-related hepatitis B reactivation. If not managed, patients may face adverse consequences such as hepatitis B reactivation-related hepatitis, liver failure, and progression of CML after forced withdrawal of medication. Therefore, this review aimed to comprehensively describe the management of CML patients with comorbid COVID-19, the pathogenesis of hepatitis B reactivation, the indicated population for prophylactic antiviral therapy, the time of antiviral drug discontinuation, and drug selection.